The Effect of Education With Animation Media and Picture Pockets on Knowledge, Attitude and Action in The Family of Pulmonary TB Patients in Preventing Transmission - Manurung, Risma Dumiri; Tambunan, Sulastri Galumbang Panahatan (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Pulmonary Tebercolosis is one of the ten leading causes of mortality and the most prevalent infectious agent. According to 2018 data from the World Health Organization, there are 10,4 million cases of pulmonary tuberculosis worldwide, 56% of which are in India, Indonesia, China, the Philippines, and Pakistan. Identifying positive smear cases based on the outcomes of pulmonary TB case detection coverage. Transmission of pulmonary TB germs by splashes of saliva while speaking, sneezing, or coughing is behavior-related, and closest contact, such as with household members, will be twice as dangerous as regular or non-home contact. To interrupt the transmission cycle of pulmonary tuberculosis, it is essential to understand the elements that drive the illness. This research intends to investigate the impact of employing animated media and illustrated pocket books to prevent the spread of pulmonary tuberculosis on the knowledge, attitudes, and behaviors of families before to and after instruction. This is a quasi-experimental study using a pretest-posttest design with a control group. There were 90 participants in the family study (wife, mother, and adult children) who had family members with pulmonary tuberculosis. They were separated into two intervention groups and one control group. Sampling through unintentional sampling. Analysis of univariate and bivariate data using paired t-test 95% CI 0.05.